PENGARUH CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSET (ROA), LOAN TO DEPOSIT RATIO (LDR) TERHADAP PERTUMBUHAN LABA PADA PT BANK MAYBANK INDONESIA Tbk. - Rinawati, Rinawati; Eko Widodo; Ririn Wahyu Arida (Cahaya Ilmu Bangsa, 2024)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Return On Asset (ROA), Loan to Deposit Ratio (LDR), on profit growth at PT Bank Maybank Indonesia Tbk. Period 2013-2020. The independent variables in this study are Capital Adequacy Ratio (CAR), Return On Asset (ROA), Loan to Deposit Ratio (LDR). The dependent variable in this study is profit growth. The population used is financial data containing Capital Adequacy Ratio (CAR), Return On Asset (ROA), Loan to Deposit Ratio (LDR), profit growth then the researcher conducted a sampling technique using the purposive sampling method. The analysis technique in this study is descriptive analysis and statistical analysis using SPSS. The results of this study indicate that simultaneously the independent variables CAR, ROA, LDR have an effect on profit growth. Partially CAR has no effect on profit growth, ROA has an effect on profit growth, LDR has no effect on profit growth. The ability of the independent variable to explain the dependent variable is 27.9%, the remaining 72.1% of the dependent variable is explained by other variables.